Decoding Cultural Obstructions in Way of organ Transplants - Varsha Gautam (Archives of Organ Transplantation - Peertechz Publications, 2020)
Apart from basic language, different aspects of an individual's culture can play its role in literacy and influence the ability of health workers to comprehend and follow instructions. The most critical goals for patients after organ transplantation are to optimize health and wellness. Low health literacy has significant health and well-being implications and increased risk to patients for negative health outcomes. The definition of death and especially brain death is a major issue in organ transplantation. The internal tendency of a particular society to donate organs is another major factor. The organ theft, organ transfers, the fragile balancing of live contributions between the recipient's benefit and potential loss to the donor and others are among the crucial ethical concerns that require active intervention. In the following study, we address the several cultural challenges facing donation of organ around the world , and is literacy the reason of less organ transplants, particularly in India.